Predictable events and excess returns: The case of dividend announcements - Kalay, A (Journal of Financial Economics, 1985)
This paper hypothesizes that the risk per unit of time and the required rate of return are higher than normal during an event period whose timing can be predicted. Consistent with this hypothesis this paper presents empirical evidence indicating that the unconditional mean rate of return, the variance of stock returns and their systematic risk are higher than ‘usual’ during dividend announcement periods. However, the documented increases in the systematic risk are not large enough to fully explain the ‘excess returns’. This finding is puzzling and hard to reconcile with existing theory.